Effectiveness of Vitamin D Supplementation in Reducing Atopic Dermatitis Severity in Children: A Meta-Analysis - Ni Putu Junika Putri; I Wayan Gede Sutadarma (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Atopic dermatitis (AD) is a chronic inflammatory skin disease that commonly affects children, with increasing prevalence worldwide. Vitamin D has demonstrated immunomodulatory effects, suggesting a potential role in AD management. This meta-analysis aimed to evaluate the effectiveness of vitamin D supplementation in reducing AD severity in children. Methods: A systematic search of PubMed, Science Direct, and Cochrane databases was conducted for randomized controlled trials (RCTs) published between 2012 and 2024, investigating the effects of vitamin D supplementation on AD in children. The primary outcome was the change in SCORAD (SCORing Atopic Dermatitis) or EASI (Eczema Area and Severity Index) scores. Meta-analysis was performed using Review Manager (RevMan 5.4) software. Results: Four RCTs met the inclusion criteria, comprising a total of 234 participants. The meta-analysis revealed a significant reduction in SCORAD scores (-2.83; 95% CI: -4.9, -0.76) and EASI scores (-0.41; 95% CI: -0.70, -0.13) in the vitamin D supplementation groups compared to the control groups. A combined analysis of both scoring systems further confirmed the overall significant effect of vitamin D in reducing AD severity (-1.57; 95% CI: -2.78, -0.36). Conclusion: Vitamin D supplementation is effective in improving AD symptoms in children. Further large-scale RCTs are warranted to determine the optimal dosage and duration of vitamin D supplementation for AD management in children.